Information Technology and Learning Methodology Amid the COVID-19 Pandemic - Hari Suparwito (International Journal of Applied Sciences and Smart Technologies, 2020)
The impact of the COVID-19 pandemic on the education sector caused schools and universities are closed. Then, teaching and learning are delivered by an online method through information and communication technology. Some issues have emerged, especially on delivering materials and the minimum requirements of online learning. The study aims to review learning methodologies and the role of information and communication technology for future learning. Heutagogy and Computational Thinking have been selected as the learning methodology for approaching digital native generation. It is no doubt that the significant role in undertaking online education is information and communication technology. Therefore, we suggested some tools to enhance learning systems, such as gamification learning, virtual labs, and social media. We also discussed new learning media using information and communication technology in education. The study's contribution is to describe technology's role in the future learning system to be used by decision-makers in implementing e-learning better.